A Política Agrícola Comum da Europa: Controvérsias e continuidade - Patrícia Nasser de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The Common Agricultural Policy (CAP) of the European Union (EU), one of the most important symbols of the European regional integration process, completed fifty years in 2012. At first glance, many of its positive aspects, which places the EU as the global largest exporter position of agri-food goods, stands strong in the defense of agricultural protectionism, position which is reflected in the European way of acting in the negotiations and the CAP as a concerned policy to ensure food security in the European Continent. All these elements show positive traits of European regional integration. However, the CAP is quite controversial because over the decades it favored the interests of the European farmers maintaining its level of income, especially of certain member states of the EU, persists for more than five decades keeping the essence of its original structure, even it is an extremely costly policy to citizens of the European bloc of regional integration and resulted in imbalances. Taking into account these elements, the purpose of this article is to discuss the origins of the CAP, which are linked to food security in the post-Second World War Europe, the interests that supported its original formulation, the previous negotiations and those that occurred during the its institutionalization process. In addition, we intend to analyze the first results of the integrated European policy in the agricultural area, which went through incremental changes until 1992.
Keywords: F02; F15; F55; 330; Common Agricultural Policy; European Union; European Economic Community; agriculture